2016
DOI: 10.1117/1.nph.3.1.015003
|View full text |Cite|
|
Sign up to set email alerts
|

Transcranial low-level laser therapy (810 nm) temporarily inhibits peripheral nociception: photoneuromodulation of glutamate receptors, prostatic acid phophatase, and adenosine triphosphate

Abstract: Abstract. Photobiomodulation or low-level light therapy has been shown to attenuate both acute and chronic pain, but the mechanism of action is not well understood. In most cases, the light is applied to the painful area, but in the present study we applied light to the head. We found that transcranial laser therapy (TLT) applied to mouse head with specific parameters (810 nm laser, 300 mW∕cm 2 , 7.2 or 36 J∕cm 2 ) decreased the reaction to pain in the foot evoked either by pressure (von Frey filaments), cold,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 42 publications
1
29
1
Order By: Relevance
“…We previously showed [7] that applying PBM with an 810 nm laser spot delivered to the head of the mouse, markedly raised the pain threshold in the hind foot with a maximum effect measured 2 hours later. In that study we also showed an analgesic effect for the response to cold, heat and inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed [7] that applying PBM with an 810 nm laser spot delivered to the head of the mouse, markedly raised the pain threshold in the hind foot with a maximum effect measured 2 hours later. In that study we also showed an analgesic effect for the response to cold, heat and inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Photobiomodulation therapy (PBMT) also known as low-level laser/light therapy (LLLT), is a rapidly growing approach to stimulate healing [5, 6], increase tissue regeneration [6] and reduce pain [7] and inflammation [8]. PBMT has no known side-effects, and as yet has shown no long-term adaptation to the treatment [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…1,3,[9][10][11][12][13] Many studies investigated the effectiveness of the transcranial NIR-PBM in clinical and normal conditions. [14][15][16][17][18] Improvement in the neurological or psychological symptoms has been reported after light irradiation in both animal and human models. 3,[19][20][21][22][23][24] The promotion of cognitive performance such as the reaction time has been observed in some cognitive studies assessed by the attentional tests or the psychomotor vigilance task (PVT).…”
Section: Introductionmentioning
confidence: 99%
“…Odontology [4]- [7] and Physiotherapy [8]. The best-known effects of the PBMT, which applies red and infrared lasers or LEDs in the treatments, are the reduction of inflammatory processes [9], improvement of wound healing [10], and reduction of pain [11].…”
Section: Introductionmentioning
confidence: 99%
“…To scan the whole specimen, either the specimen holder or the light source is moved. In the second design, on the bottom of the figure, calledepi-illuminated confocal microscope, there is only one lens(11), which works as condenser and objective lens. There is also a partial or dichromatic mirror(17).…”
mentioning
confidence: 99%